Analisis Likuiditas dan Solvabilitas untuk memprediksi Profitabilitas Pada PT. BPRS Artha Pamenang Kediri - Ana Susanti (Universitas Islam Kadiri, 2020)
Research aims to understand the influence of the ratio liquidity and solvability to profitability to pt .BPRS artha pamenang kediri the period 2013-2107 .Researchers used research methodology quantitative .Techniques used in the sample collection that is nonprobability purposive sampling .From test results on multiple linear regression analysis diketahuhi that there is the influence of significantly between current ratio (CR) and quick ratio (QR) against return on assets (ROA) while the department to asset ratio ( DAR ) there was no influence significantly to return on assets (ROA) and the department to equity ratio ( DER ) show the results of the value of the significance of as much as 0,135 meant leverage indicated in the research may be capable of 1,35 %. wrongBased on the description of the researchers can draw the conclusion that the ratio of significant impact on liquidity and solvency ratio profitability by using two proxy that is a debt to asset ratio roa and will not affect a debt to equity ratio obtained value significantly by 0,135 against roa, it means a given influence have room for error by 1,35 % which this value is still on the line a prediction.